PENYULUHAN DETEKSI DINI KANKER SERVIKS DAN PEMERIKSAAN IVA DI DESA SELAT KECAMATAN SELAT KABUPATEN KARANGASEM - Yanti, N.L.P.E.; Widyanthari, D.M.; Kusumaningsih, F.S.; Damayanti, M.R. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Cervical cancer is the highest morbidity in Indonesia and each year will increase in new cases. The most effective to reduce cervical cancer by early detection Visual Inspection Acetic Acid (VIA). Public awareness especially group of productive women age to doing VIA is low. Therefore, it is necessary to the public awareness through health education to improve the knowledge, attitudes, and practice VIA. Health education held in Selat Village of Karangasem Regency. The results showed increased of knowledge 13.7% and 10.6% of attitude. There are 50% persons from health education participants doing VIA in primary health service. All participants showed negative results.